Density and occupancy of leopard cats across different forest types in Cambodia - Pin, C; Phan, C; Kamler, JF; Rostro-García, S; Penjor, U; In, V; Crouthers, R; Macdonald, EA; Chou, S; Macdonald, DW (Springer, 2022)
The leopard cat (Prionailurus bengalensis) is the most common wild felid in Southeast Asia, yet little is known about the factors that affect their population density and occupancy in natural habitats. Although leopard cats are highly adaptable and reportedly can attain high densities in human-modified habitats, it is not clear which natural habitat is optimal for the species. Also, this felid has been preyed upon by large carnivores in Southeast Asia, yet the intra-guild effects of large carnivore presence on leopard cats are almost unknown. To shed light on these fundamental questions, we used data from camera trap surveys for felids to determine the leopard cat densities in three different forest types within Cambodia: continuous evergreen, mosaic dominated by evergreen (hereafter evergreen mosaic), and mosaic dominated by open dry deciduous forests (hereafter DDF mosaic). We also conducted occupancy analyses to evaluate the interactions of the leopard cats with three large carnivores: leopards (Panthera pardus), dholes (Cuon alpinus), and domestic dogs (Canis familiaris). The estimated density (individuals/100 km2 ± SE) was highest in the continuous evergreen (27.83 ± 7.68), followed by evergreen mosaic (22.06 ± 5.35) and DDF mosaic (13.53 ± 3.23). Densities in all three forest types were relatively high compared to previous studies. Domestic dogs were detected on all 3 sites, and leopards and dholes had sufficient records on only one site each. The occupancy probability of leopard cats was not affected by the presence or absence of any large carnivore, indicating that large carnivores and leopard cats occurred independently of each other. Our findings support the claim that leopard cats are habitat generalists, but we show that evergreen forest is the optimum natural habitat for this species in the region. The DDF mosaic appears to sustain lower densities of leopard cats, probably due to the harsh dry season and wildfires that led to reduced prey base, although this generalist felid was still able to occupy DDF in relatively moderate numbers. Overall, the adaptability of leopard cats to various forest types, and lack of negative interaction with large carnivores, helps to explain why this species is the most common and widespread felid in Southeast Asia.